Intersecções e não intersecções: os casos da Corte Interamericana de Direitos Humanos no Supremo Tribunal Federal - Magnani, Nathércia Cristina Manzano (2024)
This thesis investigated whether, how much and how the STF has discussed the convictionjs of the Inter-American Court of Human Rights. The theme gains relevance in a scneario in which controlo of conventionality is a duty of domestic courts that have adhered to the Inter-American System of Human Rights and/or that have opening clauses in their Constitutions (which is, doubly, the case of Brazil). Furthermore, also because the Judiciary bodies are fundamental actors in the implementation of transformative regional constitutionalism in Latin America, the main theoretical framework of this research. Based on an empirical survey obtained through documentary research, the thesis responded to the research problem and outlined a complete overview of the intersections found (describing, for example, their quantity, chronology, the type of action and theme in which they prevailed, among others). In the end, it was concluded that the intersection of the STF with the contentious activity of the Inter-American Court within some analytical categories that were explained at the conclusion of the work, na opportunity in which recommendations for changing the scneario were also made